Evaluating the correlation of sclerostin levels with obesity and type 2 diabetes in a multiethnic population living in Kuwait - Alramah, Tahani; Cherian, Preethi; Al-Khairi, Irina; Abu-Farha, Mohamed; Thanaraj, Thangavel Alphonse; Albatineh, Ahmed N.; Safadi, Fayez; Ali, Hamad; Abdul-Ghani, Muhammad; Tuomilehto, Jaakko; Koistinen, Heikki A.; Al-Mulla, Fahd; et al. (Frontiers in Endocrinology, 2024)
Obesity and Type 2 Diabetes Mellitus (T2DM) are intricate metabolic disorders with a multifactorial etiology, often leading to a spectrum of complications. Recent research has highlighted the impact of these conditions on bone health, with a particular focus on the role of sclerostin (SOST), a protein molecule integral to bone metabolism. Elevated circulating levels of SOST have been observed in patients with T2DM compared to healthy individuals. This study aims to examine the circulating levels of SOST in a multiethnic population living in Kuwait and to elucidate the relationship between SOST levels, obesity, T2DM, and ethnic background. The study is a cross sectionalcross-sectional analysis of